THE ECONOMIC AND ENVIRONMENTAL IMPACT OF TRANSITIONING TO ALTERNATIVE ENERGY - Sabitova Iroda Sarajiddinovna; Suyunov Komron Bakhtiyor o'g'li (PEDAGOGS, 2024)
Annotation: The paper addresses the possibility of using renewable energy sources for mechanical plant power supply. The area climatic conditions are given an assessment. The possibility to install alternative energy facilities at the plant is studied. Solar panels are proposed as alternative sources. The required equipment is selected and the calculation of the number and capacity photovoltaic cells is made. Conducted technical and economic calculations serve the basis for efficiency evaluation of installed photovoltaic cells. The purpose of the paper is to evaluate the effectiveness of alternative energy facilities integration into the power supply system of an industrial enterprise. The computation of the solar panel true power is made taking into account the table of solar insolation. The number of solar modules, inverters and other equipment connected to them has been calculated based on the area of building roofs. The economic effectiveness is estimated on the basis of the calculated payback period of the installed equipment. Assessment of Irkutsk climatic conditions has shown that the area under investigation has a relatively high potential for the development of solar energy. Therefore, this work gives a detailed consideration of the integration of solar modules into the power supply system of the industrial enterprise. Their actual power, which directly depends on solar activity and averages 80% of the capacity rate, is calculated. The calculated annual amount of power received from solar panels has showed that renewable energy facilities can make a significant part in enterprise power supply. According to the estimates obtained, the economic effectiveness of their use today is quite low. However, trends in reducing the cost of the solar panels themselves and other auxiliary equipment, as well as growth of electrical energy price make these power sources effective in the near future. The conducted study clearly shows that it is quite possible to integrate alternative energy facilities into the power supply system of an industrial enterprise, and they will be able to make a significant part of its power consumption. In view of expected drop of equipment costs and growth of electricity prices, the renewable sources will become cost-effective.